EQUIVALENT PRACTICAL RESULT BETWEEN THE DECISION IN THE CONCENTRATED CONTROL OF CONSTITUTIONALITY AND THE COLLECTIVE DECISION RECOGNIZING UNCONSTITUTIONALITY IN DIFFUSE CONTROL: THE STUDY OF THE "WIFE'S SALARY" CASE IN THE MUNICIPALITY OF SÃO CARLOS (SP) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
In this article, we intend to demonstrate that, in some cases, the effectiveness of the decision rendered with diffuse judicial review in a public civil action is equivalent to the effectiveness of the decision rendered in concentrated constitutionality control, although the corresponding processes are subject to different levels of requirements. In order to achieve the intended purpose, the first subtitle contains an examination of the constitutional basis of constitutionality control and a brief exposition of the effect of collective decisions, in diffuse control of constitutionality, with erga omnes effectiveness. The second subtitle contains a description of the problems arising from the effect of collective decisions, in diffuse control of constitutionality, with erga omnes effectiveness, and of the changes in the Public Civil Action Law aiming to circumvent them. The subsequent subheadings deal with the limitation of public civil action for the control of the constitutionality of laws or normative acts and the case study of the “wife salary” in the municipality of São Carlos (SP). The research showed that, despite the attempts to solve this incongruity, through the alteration of the Public Civil Action Law and the establishment of the understanding that the public civil action cannot be a substitute for the abstract questioning of the law in theory, there is still situations in which, in practice, the decision of the collective process with diffuse control of constitutionality produces a practical result equivalent to the decision rendered in concentrated control of constitutionality due to the object and recipients of the unconstitutional norm. The methodology used was analytical-deductive, starting from a practical case study involving the Public Ministry of São Paulo and the Public Treasury of the Municipality of São Carlos to reach the intended results.